The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1590/s1519-69842005000400015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of 5-HT1A agonist on the feeding behavior of Coturnix japonica (Galliformes: Aves)

Abstract: In this study, we investigate the effect of serotonin receptor 5-HT1A stimulation on the feeding behavior of quails (Coturnix japonica). The administration of 5-HT1A agonist, 8-OH-DPAT (0.05 to 5.0 mg/Kg) dose-dependently inhibited the food intake in normally fed quails. Greater inhibition was attained with 5.0 mg/kg (0.93 ± 0.21 g vs. 5.83 ± 0.25 g, P < 0.05, 2 h after food offer). A comparable response was obtained from previously fasted quails. At end of 2 h, a higher dose of 8-OH-DPAT induced more intense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 29 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…One of the most abundant innervating systems within the SCO is of a serotoninergic nature [28,29]. Substantial evidences have suggested that the serotoninergic system, which originates from the dorsal raphe nucleus (DRN) [30] which influence sodium appetite, food and water intake behaviors [31,32], controls the SCO secretory activity of cat, frog, lizards, and meriones [1,29,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…One of the most abundant innervating systems within the SCO is of a serotoninergic nature [28,29]. Substantial evidences have suggested that the serotoninergic system, which originates from the dorsal raphe nucleus (DRN) [30] which influence sodium appetite, food and water intake behaviors [31,32], controls the SCO secretory activity of cat, frog, lizards, and meriones [1,29,33,34].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that serotonin may exert an inhibitory action on feeding in chickens [ 47 ], GA supplementation may improve the feeding patterns and consequent carcass yield of laying hens. While some researchers have reported that an injection of a serotonin agonist reduces the food intake in the fasted–refed birds [ 48 ], others have reported an inhibitory effect on feeding patterns in fed and fasted adult quails [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the work of Kostal and Savory (1996) when female broiler breeders were injected with 40, 200 and 1000 μg/kg of the 5‐HT 1A agonist 8‐OH‐DPAT, only the highest dose of 1000 μg/kg body weight cause scratching behaviour, which is considered as part of the serotonin behaviour syndrome as described in rodents and pigeons (Kostal and Savory, 1996). Although the species’ differences cannot be disregarded, the serotonin behaviour syndrome can probably explain the inhibition of the food intake registered by Reis and Marinho (2005) in fed and fasted adult quails when doses of 500, 1000 and 5000 μg/kg of 8‐OH‐DPAT were used.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the water intake rises rapidly and significantly during the 2 h of the experiment (Saadoun and Cabrera, 2002). Recently, Reis and Marinho (2005) using the agonist 8‐OH‐DPAT showed an inhibitory effect on food intake in fed and fasted adults male quails.…”
Section: Introductionmentioning
confidence: 99%